2023
DOI: 10.1039/d3nj00755c
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt incorporation and MoS2–NiS2 heterostructure synergistic for improving full water electrolysis efficiency

Abstract: Designing a robust bifunctional water splitting catalyst at low-cost manifests great importance for water splitting. Herein, the in-situ generated MoS2/NiS2 nanosheet heterostructures by cobalt incorporation on carbon paper (Co-MoS2/NiS2/CP)have firstly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In recent years, modulating the morphology of materials is one of the effective ways to improve the water splitting performance of electrocatalysts. In recent years, researchers have reported transition metal sulfide electrocatalysts with different morphology structures, for example, one-dimensional (1D) CoS 2 nanowires 59 and Co 9 S 8 nanowires, 60 two-dimensional (2D) Co-MoS 2 /NiS 2 nanosheets, 61 and three-dimensional (3D) coral-like NiS/FeS 2 . 62 Therefore, by modulating the morphology and structure of the electrocatalysts, the active specific surface area of the catalysts can be effectively increased to expose more active sites; at the same time, the diffusion resistance of the electrolyte can be reduced to enhance the diffusion of ions and the rapid transfer rate of electrons.…”
Section: Modulation Strategies For Improving Her Catalytic Performancementioning
confidence: 99%
“…In recent years, modulating the morphology of materials is one of the effective ways to improve the water splitting performance of electrocatalysts. In recent years, researchers have reported transition metal sulfide electrocatalysts with different morphology structures, for example, one-dimensional (1D) CoS 2 nanowires 59 and Co 9 S 8 nanowires, 60 two-dimensional (2D) Co-MoS 2 /NiS 2 nanosheets, 61 and three-dimensional (3D) coral-like NiS/FeS 2 . 62 Therefore, by modulating the morphology and structure of the electrocatalysts, the active specific surface area of the catalysts can be effectively increased to expose more active sites; at the same time, the diffusion resistance of the electrolyte can be reduced to enhance the diffusion of ions and the rapid transfer rate of electrons.…”
Section: Modulation Strategies For Improving Her Catalytic Performancementioning
confidence: 99%
“…22,23 It has been both experimentally and theoretically identified that the reasonable fabrication of a heterointerface can effectively reduce the adsorption/desorption barrier of reaction intermediates via adjusting the electronic structure, the abundant defects and distorted structures as well as the strong synergistic effect between varying active sites. 24–26 For example, Sebastian et al synthesized NiFe 2 O 4 nanoparticles supported on 2H/1T multiphase MoS 2 nanosheets. 27 Due to the unique synergetic effect stemming from the strong interaction between NiFe 2 O 4 and MoS 2 , the NiFe 2 O 4 /MoS 2 heterostructured composite catalyst exhibits an outstanding ORR activity and remarkable stability.…”
Section: Introductionmentioning
confidence: 99%
“…This raises signicant concerns about the feasibility of initiating extensive research on renewable energy reservoir development and related technologies. [1][2][3] Hydrogen has high energy density and zero carbon emissions into the atmosphere, so it has shown high potential and is capable of meeting the challenges of the energy sector. Natural gas reservoirs have traditionally been converted to hydrogen via steam-reforming.…”
Section: Introductionmentioning
confidence: 99%